Effect of Expanded Graphite on Mechanical and Tribological Properties of Polyamide 6/Glass Fibre Composites - Dajana Japić; Simon Kulovec; Mitjan Kalin; Janez Slapnik; Blaž Nardin; Miroslav Huskić (Advances in Polymer Technology)
The quality of plastic gears, especially their durability, is becoming increasingly important due to advances in electric mobility. Therefore, new materials are being developed that must have better mechanical properties, high thermal conductivity for heat dissipation, and tribological properties. The composites of expanded graphite (EG) and glass fibre-reinforced polyamide 6 (PA6/GF) were prepared, and the effect of EG particle size (~5 μm (EG5) and ~1000 μm (EG1000)) on these properties was investigated. Composites with different contents (2-10 wt%) of EG in PA6/GF were prepared using a laboratory twin-screw extruder and then injection moulded in the form of rods and discs required for thermal, thermomechanical, and tribological tests. EG acted as a nucleating agent but hindered the crystallization rate at higher concentrations, which was more pronounced when EG5 was added. Dynamic mechanical analysis showed that the storage modulus increased with the addition of both types of EG. However, the addition of EG5 increased the storage modulus more than EG1000. The lowest coefficient of friction was obtained by the addition of 10 wt% EG5. The wear increased with the addition of both types of EG, only slightly with the addition of EG1000. The thermal conductivity of the composites with EG increased from 0.42 W/mK to 1 W/mK. The results show that the use of EG with smaller particle size is much more beneficial than with a larger one.